Synthetic Approaches Toward Phosphorus-Containing BODIPY and Squaraine Dyes: Enhancing Versatility of Small-Molecule Fluorophores - Jeanne M. Favret; Sergei V. Dzyuba (Molecules)
Phosphorus-containing fluorophores provide a versatile framework for tailoring photophysical properties, enabling the design of advanced fluorogenic materials for various applications. Boron dipyrromethene (BODIPY) and squaraine dyes are of interest due to their multifaceted modularity and synthetic accessibility. Incorporating phosphorus-based functional groups into BODIPY or squaraine scaffolds has been achieved through a plethora of synthetic methods, including post-dye assembly functionalization. These modifications often influence key spectroscopic properties and molecular functionality by expanding their utility in bioimaging, sensing, photosensitization, and theranostic applications. By leveraging the tunable nature of phosphorus-containing moieties, these dyes hold immense promise for addressing current challenges in spectroscopy, imaging, and material designs while unlocking new opportunities for advanced functional systems in chemistry, biology, and medicine.